Patients and Nursing Staff of Brothers of Mercy Hospital in Bratislava in the Early Modern Period (Theatrum historiae, 2013)
The study deals with the history of the Hospital of Brothers of Mercy in Bratislava in the Early Modern Time with to scope to describe it's staff and confessional, age and social structure of it's pacients. The Brothers of Mercy administered it's hospitals according to the orders observance, its personnel and admission of pacients also responded to its stipulations. The reforms of Maria Theresia and Joseph II. intervened in the all aspects of the orders life and its hospitals and also modified the staff and structure of pacients in Bratislava ́s infirmary.